Smartphone based precise monitoring method for farm operation - Caicong, Wu; Lin, Zhou; Jie, Wang; Yaping, Cai (International Journal of Agricultural and Biological Engineering, 2016)
Although Global Navigation Satellite System (GNSS) terminal has been widely used for fleet management, it cannot satisfy the need of managing changes of laborer and implement during farm operation, which are important for social service cooperatives comparing to family farms in China. The objective of this study was to explore a precise, low cost and easy-to-use method for vehicle fleet management of large scale farm machinery cooperatives. A smartphone based application software (APP) named Precise Monitoring System (PMS) was developed to record the farm operation information including tractor, implement and laborer by scanning their Quick Response codes (QR codes), and obtain real time GNSS positions by using built-in GNSS chip of smartphone. Considering the convenience usage for farmers, only two buttons, “start/pause/continue” and “stop” were designed to record farm operation status. Finally, IDs, positions and operation status were combined and transferred to the server through GPRS/3G/4G. Two kinds of experiments were designed and conducted to verify the PMS. The results showed that PMS can realize the basic functions such as precise and real-time monitoring, operation quality tracing, operation mileage and operation area calculating, and U-turn processing. The method and APP could record complex combination of production factors precisely and accurately, which is suitable for the management of vehicle fleet, and can replace GNSS terminal to some extent.Keywords: smartphone, agricultural machinery, farm operation, monitor, method, systemDOI: 10.3965/j.ijabe.20160903.2154Citation: Wu C C, Zhou L, Wang J, Cai Y P. Smartphone based precise monitoring method for farm operation. Int J Agric & Biol Eng, 2016; 9(3): 111－121.